Cu-based catalyst for catalytic conversion of carbon dioxide and preparation method of Cu-based catalyst

By introducing Mo2C support into the Cu-CeO2 catalyst, a bimetal oxide-carbide composite structure was constructed, which solved the problem of poor stability of Cu-CeO2-based catalysts at high temperatures, and achieved efficient catalytic performance and long-term stability.

CN120155223AActive Publication Date: 2025-06-17SOUTHWEST PETROLEUM UNIV

Patent Information

Application Number
CN202510313165.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-17
Publication Date
2025-06-17
Estimated Expiration
2045-03-17

AI Technical Summary

Technical Problem

Cu-CeO2-based catalysts have poor stability under high temperature conditions, weak anti-sintering ability, easy to deactivate, affecting catalytic performance.

Method used

The transition metal carbide Mo2C is used as a support to disperse the active metal Cu and nanoparticle CeO2 to build a bimetal oxide-carbide composite structure. It provides rich d-band electrons through the Mo2C support, enhances catalytic activity, and improves the stability of the catalyst through high-temperature calcination and calcination treatment.

Benefits of technology

The catalyst's adsorption, activation and conversion efficiency of reactants in the counterwater gas reaction is significantly improved, efficient catalytic performance is achieved, and long-term stability is maintained under harsh high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120155223A_ABST
    Figure CN120155223A_ABST
Patent Text Reader

Abstract

The invention discloses a Cu-based catalyst for carbon dioxide catalytic conversion and a preparation method thereof.The preparation method comprises the following steps that S1, a precursor solution providing a molybdenum source is prepared, the precursor solution and organic matter are mixed and stirred to be uniform, and a mixture is obtained; s2, drying the mixture, and performing high-temperature roasting treatment in a pure hydrogen atmosphere to obtain a Mo2C carrier; s3, dispersing the Mo2C carrier into pure water, dropwise adding a metal cation saline solution providing a copper source and a cerium source, adjusting the pH to be alkaline, stirring, aging, and filtering to obtain a precipitate; and S4, drying the precipitate in vacuum, and calcining in a pure hydrogen atmosphere to obtain the Cu-CeO2 / Mo2C catalyst. The Cu-based catalyst for the catalytic conversion of the carbon dioxide, which is high in CO2 conversion rate and CO selectivity, can be prepared, and technical support can be provided for the catalytic conversion of the CO2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and particularly relates to a Cu-based catalyst for catalytic conversion of carbon dioxide and a preparation method thereof. Background Art

[0002] At present, the energy structure in China still mainly relies on fossil fuels in the short term. In the next long period, the concentration of CO2 in the atmosphere will continue to rise, and the resulting greenhouse effect will continuously exacerbate a series of environmental problems such as global warming. In chemical industrial processes, synthetic fuels and most chemicals are produced from syngas, while the industrial application of directly using CO2 to produce high-value fuels and chemicals is lacking. Therefore, currently, the direct catalytic conversion of captured CO2 into valuable chemical raw materials such as methanol, methane, and CO by chemical technology is of great significance for "carbon emission reduction and carbon sink enhancement". Among them, the production of syngas by hydrogenation of CO2 and further conversion into more valuable hydrocarbon products through the Fischer-Tropsch reaction is one of the most practically applicable and efficient CO2 catalytic conversion technologies.

[0003] The key to improving the performance of the reverse water-gas shift (RWGS) reaction lies in the design and synthesis of high-performance catalytic materials. Among the most widely used Cu-based catalytic materials, the stability of the active interface structure is the key factor restricting the catalyst performance. In order to construct a high-performance catalyst interface structure, it is of great significance to select a suitable carrier material to enhance the interaction between the metal and the carrier. As the most typical rare earth oxide, CeO2 has a unique redox ability due to its rich source and the reversible conversion between Ce 3+ to Ce 4+ and is widely used as an excellent carrier for supported catalysts, with broad application prospects. The rich surface oxygen vacancy structure generated by CeO2 provides favorable conditions for the anchoring of active metal Cu species, the construction of a high-performance catalyst interface structure, and the activation of CO2 molecules. Well-dispersed metal Cu particles further promote the effective activation and dissociation of H2 molecules. Therefore, the supported Cu-CeO2-based catalytic materials have great potential application value in the CO2 hydrogenation reaction.

[0004] However, since the RWGS reaction is an endothermic reaction and is favorable for the formation of CO at high temperatures, the above-mentioned Cu-CeO2-based catalysts have poor stability and weak anti-sintering ability at high temperatures and are prone to deactivation, which seriously affects the catalytic performance. Therefore, constructing a stable Cu-CeO2-based catalyst interface and improving the long-term high-temperature stability of Cu-based catalytic materials have become difficult problems to be solved urgently. Summary of the Invention

[0005] Aiming at the above problems, the present invention aims to provide a Cu-based catalyst for catalytic conversion of carbon dioxide and a preparation method thereof.

[0006] The technical solution of the present invention is as follows:

[0007] On the one hand, a preparation method of a Cu-based catalyst for carbon dioxide catalytic conversion is provided, including the following steps:

[0008] S1: Prepare a precursor solution providing a molybdenum source, mix the precursor solution with an organic substance, and stir evenly to obtain a mixture;

[0009] S2: Dry the mixture, and then perform high-temperature calcination treatment under a pure hydrogen atmosphere to obtain a Mo2C support;

[0010] S3: Disperse the Mo2C support in pure water, and drop in an aqueous solution of metal cations providing a copper source and a cerium source, adjust the pH to alkaline, stir, age, and filter to obtain a precipitate;

[0011] S4: Dry the precipitate in vacuum, and then calcine it under a pure hydrogen atmosphere to obtain a Cu-CeO2 / Mo2C catalyst.

[0012] Preferably, in step S1, the solute of the precursor solution is any one or more of ammonium molybdate tetrahydrate, sodium molybdate, and molybdenum chloride.

[0013] Preferably, in step S1, the organic substance is any one or more of sucrose, glucose, maltose, lactose, fructose, cellobiose, D-xylose, xylitol, erythritol, and sorbitol.

[0014] Preferably, in step S1, the molar ratio of the solute of the precursor solution to the organic substance is 1:1 - 10.

[0015] Preferably, in step S1, when stirring, the temperature is 10 - 30°C and the time is 0.1 - 5 h; in step S2, when drying, the temperature is 50 - 130°C and the time is 10 - 48 h; in step S2, when performing high-temperature calcination, the heating rate is 1 - 10°C / min, the temperature is 400 - 600°C, and the time is 10 - 48 h.

[0016] Preferably, in step S3, the solute of the aqueous solution of metal cations is a mixed salt of a copper salt and a cerium salt. The copper salt is any one or more of copper nitrate trihydrate, copper chloride dihydrate, copper sulfate pentahydrate, and copper acetate. The cerium salt is any one or more of cerium nitrate hexahydrate, cerium chloride heptahydrate, cerous sulfate, cerium acetate, and ammonium cerium nitrate. The molar ratio of the copper salt, the cerium salt, and the Mo2C support is 1:1:50 - 30:30:50.

[0017] Preferably, in step S3, an inorganic salt solution with a concentration of 0.1 - 15 mol / L is used to adjust the pH to 8 - 10, and the solute of the inorganic salt solution is any one or more of urea, ammonium carbonate, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, ammonia water, sodium hydroxide, and potassium hydroxide.

[0018] Preferably, in step S3, when stirring, the temperature is 10 - 80 °C and the time is 0.1 - 2 h; when aging, the temperature is 10 - 80 °C and the time is 0.1 - 2 h.

[0019] Preferably, in step S4, when drying, the temperature is 50 - 100 °C and the time is 4 - 48 h; when calcining, the heating rate is 1 - 10 °C / min, the temperature is 400 - 800 °C, and the time is 1 - 8 h.

[0020] On the other hand, a Cu-based catalyst for carbon dioxide catalytic conversion is also provided, which is prepared by using the preparation method of the Cu-based catalyst for carbon dioxide catalytic conversion described in any one of the above.

[0021] The beneficial effects of the present invention are as follows:

[0022] (1) The present invention uses transition metal carbide as a carrier, and at the same time disperses the active metal Cu and the nanoparticle CeO2 to construct a novel bimetallic oxide-carbide composite structure. The three components of Cu, CeO2, and Mo2C interact with each other, enabling the active sites to synergistically promote the reaction, greatly improving the adsorption, activation, and conversion efficiency of the reactants in the reverse water gas shift reaction, and achieving high catalytic performance with a unique active site network structure.

[0023] (2) The present invention prepares a Cu-CeO2 / Mo2C catalyst with multi-active site synergy through a simple synthesis method. The metal Cu species and CeO2 nanoparticles are highly dispersed on the Mo2C carrier, constructing a stable catalytic active interface. Cu, as an active metal, has good hydrogenation activity and plays an important role in the dissociation of H2; CeO2 can provide abundant oxygen vacancies to promote the adsorption and activation of CO2; Mo2C, as a carrier, has a special electronic structure and catalytic performance, which helps to improve the activity and selectivity of the RWGS reaction.

[0024] (3) When the catalyst prepared by the present invention is applied to the reverse water gas shift reaction, it exhibits good catalytic activity under harsh reaction conditions (600 °C, the mass space velocity GHSV is 200,000 mL·g cat -1 ·h -1)Under such conditions, the CO2 conversion rate can reach 65.12%, and the CO selectivity is 100%, showing great potential for industrial applications. Compared with traditional catalysts, this system can also achieve high catalytic activity at a lower temperature (400 °C), and the CO2 conversion rate can reach 32.09%, thus reducing energy consumption and equipment requirements. Description of the Drawings

[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for use in the description of the embodiments or the prior art. Obviously, the drawings in the following description are only some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on these drawings.

[0026] Figure 1 XRD pattern of Example 3.

[0027] Figure 2 Schematic diagram of the CO2 conversion rate test results of the catalysts of each example at different temperatures; among them, (a) is the CO2 conversion rate of Examples 1-5 at a mass space velocity GHSV of 200,000 mL·g cat -1 ·h -1 and (b) is the CO2 conversion rate of Examples 2 and 6 at a mass space velocity GHSV of 100,000 mL·g cat -1 ·h -1 .

[0028] Figure 3 Schematic diagram of the stability test results of Example 3 at 600 °C and a mass space velocity GHSV of 200,000 mL·g cat -1 ·h -1 . Detailed Embodiments

[0029] The present invention will be further described below in conjunction with the drawings and embodiments. It should be noted that, without conflict, the embodiments in the present application and the technical features in the embodiments can be combined with each other. It should be pointed out that unless otherwise specified, all technical and scientific terms used in the present application have the same meaning as commonly understood by those of ordinary skill in the technical field to which the present application belongs. The terms "including" or "comprising" and the like used in the present invention disclosure mean that the elements or objects appearing before the term cover the elements or objects listed after the term and their equivalents, without excluding other elements or objects.

[0030] On the one hand, the present invention provides a preparation method for a Cu-based catalyst for catalytic conversion of carbon dioxide, comprising the following steps:

[0031] S1: Prepare a precursor solution providing a molybdenum source, mix the precursor solution with an organic substance, and stir evenly to obtain a mixture.

[0032] In a specific embodiment, the solute of the precursor solution is any one or more of ammonium molybdate tetrahydrate, sodium molybdate, and molybdenum chloride, the organic substance is any one or more of sucrose, glucose, maltose, lactose, fructose, cellobiose, D-xylose, xylitol, erythritol, and sorbitol, and the molar ratio of the solute of the precursor solution to the organic substance is 1:1 - 10.

[0033] In a specific embodiment, when stirring, the temperature is 10 - 30°C and the time is 0.1 - 5 h.

[0034] S2: Dry the mixture, and then perform high-temperature calcination treatment under a pure hydrogen atmosphere to obtain a Mo₂C support.

[0035] In a specific embodiment, when drying, the temperature is 50 - 130°C and the time is 10 - 48 h; when performing high-temperature calcination, the heating rate is 1 - 10°C / min, the temperature is 400 - 600°C, and the time is 10 - 48 h.

[0036] S3: Disperse the Mo₂C support in pure water, and drop in an aqueous solution of metal cation salts providing a copper source and a cerium source, adjust the pH to alkaline, stir, age, and filter to obtain a precipitate.

[0037] In a specific embodiment, the solute of the aqueous solution of metal cation salts is a mixed salt of a copper salt and a cerium salt, the copper salt is any one or more of copper nitrate trihydrate, copper chloride dihydrate, copper sulfate pentahydrate, and copper acetate, the cerium salt is any one or more of cerium nitrate hexahydrate, cerium chloride heptahydrate, cerous sulfate, cerium acetate, and ammonium cerium nitrate; the molar ratio of the copper salt, cerium salt, and Mo₂C support is 1:1:50 - 30:30:50.

[0038] In a specific embodiment, an inorganic salt solution with a concentration of 0.1 - 15 mol / L is used to adjust the pH to 8 - 10, and the solute of the inorganic salt solution is any one or more of urea, ammonium carbonate, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, ammonia water, sodium hydroxide, and potassium hydroxide.

[0039] In a specific embodiment, when stirring, the temperature is 10 - 80°C and the time is 0.1 - 2 h; when aging, the temperature is 10 - 80°C and the time is 0.1 - 2 h.

[0040] S4: Place the precipitate in a vacuum for drying, and then calcine it in a pure hydrogen atmosphere to obtain the Cu-CeO2 / Mo2C catalyst.

[0041] In a specific embodiment, when drying, the temperature is 50 - 100 °C and the time is 4 - 48 h; when calcining, the heating rate is 1 - 10 °C / min, the temperature is 400 - 800 °C, and the time is 1 - 8 h.

[0042] In the present invention, by introducing Mo2C, a stable Cu-CeO2 catalytic interface can be constructed. The introduction of carbon in Mo2C provides abundant d-band electrons for the material, significantly enhancing its catalytic activity. Mo2C is used as the carrier material of the catalyst, which not only helps to disperse the active metal and oxide components, but also provides sufficient space and coordination environment for these components, forming a more stable metal-oxide interface structure, improving the catalytic reaction performance, achieving high stability of the catalyst, and being able to be hailed as a "platinum-like catalyst".

[0043] On the other hand, the present invention also provides a Cu-based catalyst for catalytic conversion of carbon dioxide, which is prepared by using the preparation method of the Cu-based catalyst for catalytic conversion of carbon dioxide described in any one of the above.

[0044] In a specific embodiment, the catalyst of the present invention is used in the reverse water-gas shift reaction, and the reduction activation conditions are as follows: The catalyst and quartz sand are loaded into a quartz tube fixed-bed reactor, and a hydrogen-containing mixed gas is introduced for reduction. The volume percentage of hydrogen in the hydrogen-containing mixed gas is 5 - 100%, and the remaining gas is nitrogen, argon or helium. The reduction temperature is 300 - 600 °C, the pressure is 0.1 - 3 MPa, and the mass space velocity is 60000 - 500000 mL·g cat -1 ·h -1 , and the activation time is 1 - 10 h.

[0045] The evaluation conditions for the reverse water-gas shift reaction are as follows: The reaction gas is introduced, and the molar ratio of hydrogen to carbon dioxide in the reaction gas is 9:1 - 1:1, with nitrogen as the diluent gas; the mass space velocity is 60000 - 500000 mL·g cat -1 ·h -1 , the reaction pressure is 0.1 - 5 Mpa, and the reaction temperature is 300 - 800 °C.

[0046] Example 1

[0047] A Cu-based catalyst for catalytic conversion of carbon dioxide is prepared by the following steps:

[0048] (1) Dissolve 7.4 mmol of ammonium molybdate tetrahydrate in 70 mL of deionized water (DI). After stirring at room temperature for 30 min, add 15.2 mmol of sucrose. Stir the mixed solution for 0.5 h to obtain a homogeneous solution. Place the above solution in an oven at 110 °C and dry it overnight. Grind the dried sample into powder in an agate mortar. Finally, calcine it at a high temperature of 500 °C in pure H₂ for 12 h with a heating rate of 10 °C / min to obtain the Mo₂C support.

[0049] (2) Take 1 g of the Mo₂C support and disperse it in 50 mL of ultrapure water, and stir for 10 min at room temperature. Then dissolve copper(II) chloride dihydrate and cerium(III) chloride heptahydrate in 25 mL of ultrapure water. The molar ratio of the copper salt, cerium salt and Mo₂C support is 3:2:50. Next, drop the aqueous solution of metal cation salts composed of copper(II) chloride dihydrate and cerium(III) chloride heptahydrate into the dispersion of the Mo₂C support; at the same time, add potassium carbonate solution (0.60 mol / L) to adjust the pH of the mixed solution to 10, stir for 20 min, age for 40 min, wash with ultrapure water at room temperature, then dry in a vacuum oven at 80 °C for 12 h, and calcine in pure H₂ at 500 °C for 12 h (heating rate is 5 °C / min) to obtain the catalyst denoted as Cat1.

[0050] Example 2

[0051] A Cu-based catalyst for catalytic conversion of carbon dioxide is prepared by the following steps:

[0052] (1) Dissolve 3.5 mmol of sodium molybdate in 100 mL of deionized water (DI). After stirring at room temperature for 30 min, add 9.6 mmol of glucose. Stir the mixed solution for 4 h to obtain a homogeneous solution. Place the above solution in an oven at 110 °C and dry it overnight. Grind the dried sample into powder in an agate mortar. Finally, calcine it at a high temperature of 500 °C in pure H₂ for 15 h with a heating rate of 10 °C / min to obtain the Mo₂C support.

[0053] (2) Take 1 g of the Mo₂C support and disperse it in 50 mL of ultrapure water, and stir for 10 min at room temperature. Then dissolve copper(II) nitrate trihydrate and cerium(III) nitrate hexahydrate in 25 mL of ultrapure water. The molar ratio of the copper salt, cerium salt and Mo₂C support is 10:4:50. Next, drop the aqueous solution of metal cation salts composed of copper(II) nitrate trihydrate and cerium(III) nitrate hexahydrate into the dispersion of the Mo₂C support; at the same time, add sodium carbonate solution (0.50 mol / L) to adjust the pH of the mixed solution to 9, stir for 25 min, age for 25 min, wash with ultrapure water at room temperature, then dry in a vacuum oven at 70 °C for 10 h, and calcine in pure H₂ at 500 °C for 9 h (heating rate is 5 °C / min) to obtain the catalyst denoted as Cat2.

[0054] Example 3

[0055] A Cu-based catalyst for catalytic conversion of carbon dioxide is prepared by the following steps:

[0056] (1) Dissolve 7.4 mmol of ammonium molybdate tetrahydrate in 70 mL of deionized water (DI). After stirring at room temperature for 30 min, add 15.2 mmol of sucrose. Stir the mixed solution for 0.7 h to obtain a homogeneous solution. Place the above solution in an oven at 120 °C and dry it overnight. The dried sample is ground into powder in an agate mortar. Finally, it is calcined at a high temperature of 500 °C in pure H2 for 20 h with a heating rate of 10 °C / min to obtain the Mo2C support.

[0057] (2) Take 1 g of the Mo2C support and disperse it in 50 mL of ultrapure water, and stir at room temperature for 10 min. Then dissolve copper nitrate trihydrate and cerium nitrate hexahydrate in 25 mL of ultrapure water, and the molar ratio of the copper salt, cerium salt and Mo2C support is 10:3:50. Next, drop the aqueous solution of metal cations composed of copper nitrate trihydrate and cerium nitrate hexahydrate into the dispersion of the Mo2C support; at the same time, add a sodium bicarbonate solution (0.5 mol / L) to adjust the pH of the mixed solution to 9, stir for 30 min, age for 1 h, wash with ultrapure water at room temperature, then dry in a vacuum oven at 70 °C for 11 h, and calcine in pure H2 at 500 °C for 4 h (heating rate is 5 °C / min) to obtain the catalyst denoted as Cat3.

[0058] Example 4

[0059] A Cu-based catalyst for catalytic conversion of carbon dioxide is prepared by the following steps:

[0060] (1) Dissolve 9 mmol of ammonium molybdate tetrahydrate in 100 mL of deionized water (DI). After stirring at room temperature for 30 min, add 21.3 mmol of maltose. Stir the mixed solution for 2 h to obtain a homogeneous solution. Place the above solution in an oven at 120 °C and dry it overnight. The dried sample is ground into powder in an agate mortar. Finally, it is calcined at a high temperature of 500 °C in pure H2 for 17 h with a heating rate of 10 °C / min to obtain the Mo2C support.

[0061] (2) Disperse 1 g of the Mo2C support in 50 mL of ultrapure water and stir for 10 min at room temperature. Then dissolve copper sulfate pentahydrate and cerium sulfate in 25 mL of ultrapure water. The molar ratio of the copper salt, cerium salt, and Mo2C support is 8:5:50. Next, drop the aqueous solution of metal cations composed of copper sulfate pentahydrate and cerium sulfate into the dispersion of the Mo2C support; at the same time, add a potassium bicarbonate solution (1.0 mol / L) to adjust the pH of the mixed solution to 8, stir for 10 min, age for 10 min, wash with ultrapure water at room temperature, then dry in a vacuum oven at 80 °C for 13 h, and calcine in pure H2 at 500 °C for 7 h (heating rate: 5 °C / min). The obtained catalyst is denoted as Cat4.

[0062] Example 5

[0063] A Cu-based catalyst for catalytic conversion of carbon dioxide is prepared by the following steps:

[0064] (1) Dissolve 5 mmol of ammonium molybdate tetrahydrate in 80 mL of deionized water (DI), stir at room temperature for 30 min, and then add 12.4 mmol of sucrose. Stir the mixed solution for 0.4 h to obtain a homogeneous solution. Place the above solution in an oven at 120 °C and dry overnight. The dried sample is ground into powder in an agate mortar. Finally, calcine in pure H2 at a high temperature for 20 h, the high-temperature calcination temperature is 500 °C, and the heating rate is 10 °C / min to obtain the Mo2C support.

[0065] (2) Disperse 1 g of the Mo2C support in 50 mL of ultrapure water and stir for 10 min at room temperature. Then dissolve copper nitrate trihydrate and cerium nitrate hexahydrate in 25 mL of ultrapure water. The molar ratio of the copper salt, cerium salt, and Mo2C support is 12:3:50. Next, drop the aqueous solution of metal cations composed of copper nitrate trihydrate and cerium nitrate hexahydrate into the dispersion of the Mo2C support; at the same time, add an ammonia water solution (14.0 mol / L) to adjust the pH of the mixed solution to 9, stir for 30 min, age for 30 min, wash with ultrapure water at room temperature, then dry in a vacuum oven at 70 °C for 16 h, and calcine in pure H2 at 500 °C for 4 h (heating rate: 5 °C / min). The obtained catalyst is denoted as Cat5.

[0066] Example 6

[0067] A Cu-based catalyst for catalytic conversion of carbon dioxide is prepared by the following steps:

[0068] (1) Dissolve 7.4 mmol of ammonium molybdate tetrahydrate in 70 mL of deionized water (DI). After stirring at room temperature for 30 min, add 13.6 mmol of fructose. Stir the mixed solution for 0.5 h to obtain a homogeneous solution. Place the above solution in an oven at 110 °C and dry it overnight. The dried sample is ground into powder in an agate mortar. Finally, calcine it at a high temperature of 500 °C in pure H2 for 15 h with a heating rate of 10 °C / min to obtain the Mo2C support.

[0069] (2) Take 1 g of the Mo2C support and disperse it in 50 mL of ultrapure water, and stir for 10 min at room temperature. Then dissolve copper acetate and cerium acetate in 25 mL of ultrapure water, and the molar ratio of the copper salt, cerium salt and Mo2C support is 5:5:50. Next, drop the aqueous solution of metal cations composed of copper acetate and cerium acetate into the dispersion of the Mo2C support; at the same time, add potassium carbonate solution (0.60 mol / L) to adjust the pH of the mixed solution to 10, stir for 15 min, age for 30 min, wash with ultrapure water at room temperature, and then dry in a vacuum oven at 70 °C for 15 h, and calcine in pure H2 at 500 °C for 9 h (heating rate is 5 °C / min) to obtain the catalyst denoted as Cat6.

[0070] Comparative Example 1

[0071] A Cu-based catalyst for catalytic conversion of carbon dioxide is prepared by the following steps:

[0072] (1) Take 5.21 g of cerium nitrate hexahydrate and place it in a beaker, dissolve it with 10 mL of pure water, then add the prepared 40 mL of 15 mol / L NaOH solution, stir at room temperature for 30 min, transfer it to a 100 mL autoclave, and keep it at 180 °C in an oven for 24 h. After the reaction, wash the product with pure water until neutral, then perform suction filtration and dry overnight, and then calcine in air at 400 °C for 4 h to finally obtain the CeO2 support.

[0073] (2) Take 1 g of the CeO2 support and disperse it in 50 mL of ultrapure water, and stir for 10 min at room temperature. Then dissolve copper nitrate trihydrate in 25 mL of ultrapure water, and the molar ratio of the copper salt and CeO2 support is 10:50. Next, drop the aqueous solution of metal cations composed only of copper nitrate trihydrate into the dispersion of the CeO2 support; at the same time, add sodium bicarbonate solution (0.5 mol / L) to adjust the pH of the mixed solution to 9, stir for 30 min, age for 1 h, wash with ultrapure water at room temperature, and then dry in a vacuum oven at 70 °C for 11 h, and calcine in pure H2 at 500 °C for 4 h (heating rate is 5 °C / min) to obtain the catalyst denoted as Cat7.

[0074] Test Example

[0075] The XRD patterns of the catalysts of each example and each comparative example were observed using an X-ray diffractometer. The XRD pattern of Example 3 is as Figure 1 shown. It can be seen from Figure 1 that the XRD diffraction peaks of the Cat 3 catalyst in Example 3 of the present invention coincide with the standard diffraction peak positions of Mo2C (PDF#65-8766), indicating the presence of the Mo2C phase in the Cat 3 catalyst. And there are no obvious diffraction peak intensities of Cu or CuO and CeO2, indicating that the active metal Cu and the nanoparticles CeO2 are highly dispersed on the Mo2C support, forming more catalytic active interfaces.

[0076] The catalysts of each example and each comparative example were loaded into a quartz tube fixed-bed reactor with an inner diameter of 10 mm, and 100% H2 was introduced and heated to 600 °C for reduction for 1 h. During the reverse water-gas shift reaction evaluation, a H2 / CO2 gas stream was introduced at a feed ratio of 4:1, and the test temperature range was 300-600 °C. Taking 300 °C, 350 °C, 400 °C, 450 °C, 500 °C, 550 °C, and 600 °C as one temperature point respectively, the composition of the product was analyzed and detected online using a Gasboard 3100 infrared gas analyzer. The test results are as Figure 2 shown in Table 1. The conversion rate of CO2 and the selectivity of CO were calculated according to the following formulas:

[0077]

[0078] where: C CO2 is the conversion rate of carbon dioxide; [CO] is the molar concentration of carbon monoxide; [CH4] is the molar concentration of methane; [CO2] is the molar concentration of carbon dioxide; S CO is the selectivity of the catalyst for carbon monoxide.

[0079] Table 1 Catalyst activity test results at 600 °C

[0080]

[0081] It can be seen from Table 1 that the catalyst of the present invention is at atmospheric pressure and the mass space velocity is 200,000 mL·gcat -1 ·h -1Under high space velocity conditions, it shows excellent carbon dioxide conversion rate. In all examples, the CO selectivity of the catalyst is nearly 100%. From the catalytic activity data of CO2 conversion rate, the catalysts in each example all show relatively good catalytic activity. In sharp contrast, the catalytic activity of the catalyst in Comparative Example 1 is low. This indicates that the introduction of Mo2C significantly improves the performance of the catalyst, probably because a strong metal-support interaction is constructed between Mo2C and Cu, CeO2, which promotes the formation and activation of reactive sites on the catalyst surface and enhances the adsorption and conversion ability of CO2.

[0082] Combined with Figure 2 It can be seen that the Cat 3 catalyst shows excellent performance under harsh conditions (600 °C, mass space velocity GHSV is 200,000 mL·gcat -1 ·h -1 ), with a CO2 conversion rate of 65.12% and a CO selectivity of 100%, showing significant industrial application potential. The Cat 2 catalyst can still achieve relatively high catalytic activity at a lower temperature (400 °C), with a CO2 conversion rate of 32.09% and a CO selectivity of 100%, effectively reducing energy consumption and equipment requirements.

[0083] Combined with Figure 3 From the performance analysis of the Cat 3 catalyst, under the harsh reaction conditions of 600 °C and a mass space velocity GHSV of up to 200,000 mL·gcat -1 ·h -1 , this catalyst shows excellent high-temperature stability. At the initial stage of the reaction, the CO2 conversion rate is as high as 65.12%, fully proving that the Cat 3 catalyst has the activity to efficiently drive the conversion of CO2 at the initial stage and can quickly activate the reaction path. As the reaction time extends, after 40 h, the CO2 conversion rate stabilizes at about 50%, indicating that the catalyst system enters the steady-state activity stage. From an in-depth analysis of the catalytic mechanism, this stability shows that after the initial reaction, although the active sites of the Cat 3 catalyst may be covered by carbon deposition or undergo structural micro-adjustment, it can still maintain stable catalytic efficiency, indicating that its active sites have anti-deactivation ability under high-temperature and high-space velocity conditions.

[0084] In summary, the present invention can provide a Cu-CeO2 / Mo2C catalyst with high catalytic activity. Compared with the prior art, the present invention has made significant progress.

[0085] As described above, these are only representative embodiments of the present invention and do not impose any formal restrictions on the present invention. Any person skilled in the relevant art can, without departing from the scope of the technical solution of the present invention, make some modifications or improvements using the technical content disclosed above, and such embodiments are equivalent embodiments of the present invention. However, as long as the content does not depart from the technical solution of the present invention, any simple modification, equivalent change, and improvement made to the above embodiments based on the technical essence of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a Cu-based catalyst for catalytic conversion of carbon dioxide, characterized in that: The following steps are involved: S1: preparing a precursor solution for providing a molybdenum source, and mixing the precursor solution with an organic matter, stirring evenly to obtain a mixture; S2: drying the mixture, and then calcining it at high temperature in a pure hydrogen atmosphere to obtain a Mo2C carrier; S3: dispersing the Mo2C carrier into pure water, and dropping a metal cation salt aqueous solution providing a copper source and a cerium source, adjusting the pH to alkaline, stirring, aging, and filtering to obtain a precipitate; S4: drying the precipitate in a vacuum, and then calcining the precipitate in a pure hydrogen atmosphere to obtain a Cu-CeO2 / Mo2C catalyst.

2. The method for preparing a Cu-based catalyst for catalytic conversion of carbon dioxide according to claim 1, characterized in that: In step S1, the solute of the precursor solution is any one or more of ammonium molybdate tetrahydrate, sodium molybdate, and molybdenum chloride.

3. The method for preparing a Cu-based catalyst for catalytic conversion of carbon dioxide according to claim 1, characterized in that: In step S1, the organic matter is any one or more of sucrose, glucose, maltose, lactose, fructose, cellobiose, D-xylose, xylitol, erythritol, and sorbitol.

4. The method for preparing a Cu-based catalyst for catalytic conversion of carbon dioxide according to claim 1, characterized in that: In step S1, the molar ratio of the solute in the precursor solution to the organic matter is 1:1-10.

5. The method for preparing a Cu-based catalyst for catalytic conversion of carbon dioxide according to claim 1, characterized in that: In step S1, when stirring is performed, the temperature is 10-30°C and the time is 0.1-5h; in step S2, when drying is performed, the temperature is 50-130°C and the time is 10-48h; in step S2, when high-temperature calcination is performed, the heating rate is 1-10°C / min, the temperature is 400-600°C and the time is 10-48h.

6. The method for preparing a Cu-based catalyst for catalytic conversion of carbon dioxide according to claim 1, characterized in that: In step S3, the solute of the metal cation salt solution is a mixed salt of a copper salt and a cerium salt, the copper salt is any one or more of copper nitrate trihydrate, copper chloride dihydrate, copper sulfate pentahydrate, and copper acetate, and the cerium salt is any one or more of cerium nitrate hexahydrate, cerium chloride heptahydrate, cerous sulfate, cerium acetate, and ammonium cerium nitrate; the molar ratio of the copper salt, the cerium salt, and the Mo2C carrier is 1:1:50-30:30:

50.

7. The method for preparing a Cu-based catalyst for catalytic conversion of carbon dioxide according to claim 1, characterized in that: In step S3, an inorganic salt solution with a concentration of 0.1-15 mol / L is used to adjust the pH to 8-10, and the solute of the inorganic salt solution is any one or more of urea, ammonium carbonate, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, ammonia water, sodium hydroxide, and potassium hydroxide.

8. The method for preparing a Cu-based catalyst for catalytic conversion of carbon dioxide according to claim 1, characterized in that: In step S3, the stirring is performed at a temperature of 10-80° C. and a time of 0.1-2 h; and the aging is performed at a temperature of 10-80° C. and a time of 0.1-2 h.

9. The method for preparing a Cu-based catalyst for catalytic conversion of carbon dioxide according to claim 1, characterized in that: In step S4, when drying is performed, the temperature is 50-100° C. and the time is 4-48 hours; when calcining is performed, the heating rate is 1-10° C. / min, the temperature is 400-800° C. and the time is 1-8 hours.

10. A Cu-based catalyst for catalytic conversion of carbon dioxide, characterized in that: The catalyst is prepared by the method for preparing a Cu-based catalyst for catalytic conversion of carbon dioxide as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of supported Ni-MoCx catalytic material and application of supported Ni-MoCx catalytic material to prepare synthetic gas by chemical-looping dry gas reforming

    CN109894133A

  • Energy-efficient system and method for carbon dioxide conversion

    CN112105593A

  • Method for preparing methanol through carbon dioxide hydrogenation based on molybdenum carbide catalyst

    CN113398961A

  • Fe / CeO2 catalyst for preparing synthesis gas through reverse water gas reaction

    CN115814803A

  • Method of producing a catalyst structure comprising molybdenum carbide, and catalyst structure comprising molybdenum carbide

    WO2025003372A1

Cited By

  • Epoxy resin composite material with adjustable degradation performance and preparation method thereof

    CN121825172A